Establishing a gender-sensitive model of disaster relief and preparedness:A focus on relief and preparedness in the case of flood disaster. - Selamat, Nor Hafizah (Universiti Sains Malaysia, 2016)
The overall objective of this study is to understand, whether gender has been adequately addressed in the local disaster management plan and its consequences. This study includes three focus group discussions involving 23 women of flood victims in three different districts in Kelantan, namely Pasir Mas, Tumpet and Kota Bharu. In-depth interviews were carried out with three individuals, one from each districts, in addition to a total of 298 survey questionnaire manage to be collected. The study revealed that women were more vulnerable to the flood disaster compared to men, due to differences in gendered social roles, social norms and restrictions goveming behaviour